ANALISIS PERKEMBANGAN JUMLAH FASILITAS DAN PENGUNJUNG DI KETAPANG URBAN AQUACULTURE MAUK TANGERANG BANTEN - Nun Nishfatin; Hasan Hasan; Adiyat Nuryasin; Devi Faustine Elvina Nuryadin (Jurnal Perikanan Pantura (JPP), 2024)
Ketapang Urban Aquaculture (KUA) has important potential as a sector that can contribute to meeting food needs, developing the local economy and preserving the environment. This ecotourism development is a program from the Tangerang Regent as stated in Tangerang Regency Regional Regulation Number 1 of 2019 concerning the Medium Term Development Plan for the Tangerang Regency Region for 2019-2023. The problems that occur in tourist areas are tourism that can only last for a short time due to various factors and environmental damage caused by the development of facilities as well as visitors who do not pay attention to the carrying capacity of the area. This research aims to analyze the development of facilities, visitors and management in the Ketapang Urban Aquaculture Mauk Tangerang Banten mangrove tourism area so that it becomes a sustainable ecotourism. The research was carried out at Ketapang Urban Aquaculture Mauk Tangerang Banten starting from January-February 2024. This research is quantitative descriptive. Data collection stages, namely primary and secondary data collection. The data collection method was carried out by field surveys and interviews with managers of the KUA tourist area. The results of data on the development of facilities during their inception have not yet been redeveloped. Meanwhile, the development of the number of visitors is uncertain, with the highest number of visits obtained in April 2023, namely 30,157 people and the lowest in November 2023, 3,321 people. The management of Ketapang Urban Aquaculture (KUA) is also contained in the Regent Regulation Number 89 of 2022 which is the reference framework for KUA management. The recommendations that can be made by Ketapang Urban Aquaculture (KUA) are to provide several additional facilities that can attract visitors by paying attention to the carrying capacity of the area and carrying out evaluations based on visitor assessments. Facility development can be done with appropriate KUA management and marketing strategies.